Continuous femoral nerve block versus fascia iliaca compartment block as postoperative analgesia in patients with hip fracture - Temelkovska Stevanovska, Marina; Durnev, Vesna; Jovanovski -Srceva, Marija; Mojsova-Mijovska, Maja; Trpeski, Sime (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/ Sciendo, 2014)
Systemic postoperative analgesia is inefficient in most patients with hip fracture, which is the reason for pain, especially during leg movement. Peripheral and plexus nerve blocks are an efficient option for postoperative pain relief. The aim of this study was to compare the effect and duration of continuous FNB versus a single FIC block as a postoperative analgesia in patients with hip fracture.
Keywords: postoperative analgesia; regional anesthesia; fascia iliaca compartment block; femoral nerve block; hip fracture